Patient grouping for dose surveys and establishment of diagnostic reference levels in paediatric computed tomography. Issue 1 (1st April 2015) - Vassileva, J.; Rehani, M.
Abstract : There has been confusion in literature on whether paediatric patients should be grouped according to age, weight or other parameters when dealing with dose surveys. The present work aims to suggest a pragmatic approach to achieve reasonable accuracy for performing patient dose surveys in countries with limited resources. The analysis is based on a subset of data collected within the IAEA survey of paediatric computed tomography (CT) doses, involving 82 CT facilities from 32 countries in Asia, Europe, Africa and Latin America. Data for 6115 patients were collected, in 34.5 % of which data for weight were available. The present study suggests that using four age groups, <1, >1–5, >5–10 and >10–15 y, is realistic and pragmatic for dose surveys in less resourced countries and for the establishment of DRLs. To ensure relevant accuracy of results, data for >30 patients in a particular age group should be collected if patient weight is not known. If a smaller sample is used, patient weight should be recorded and the median weight in the sample should be within 5–10 % from the median weight of the sample for which the DRLs were established. Comparison of results from different surveys should always be performed with caution, taking into consideration the way of grouping of paediatric patients. Dose results can be corrected for differences in patient weight/age group.